Osądy Kiry w mandze „Death Note” a problem kultury okrucieństwa - Jarosław Dobrzycki (Literatura i Kultura Popularna)
Cruelty and violence have been a part of our culture for centuries. They accompanied society at the turn of various periods. This phenomenon gradually evolved from gladiatorial fights to violent television programs. Nowadays, the media — especially television — are treated like ancient arenas where battles were fought to the viewers’ delight. The culture of cruelty is also seen in the Death Note manga. In this paper I will show that the judgments made by the protagonist are presented by the media in the generic guise of a show. With Geoffrey Gorer’s notion of ‘the pornography of death,’ Louis-Vincent Thomas’s ‘cannibalism of the eye,’ as well as the issues related to the culture of cruelty as understood by Marek Krajewski, I will examine and prove that the main character’s actions have become a part of the media spectacle of death, and are eventually reduced to mass entertainment. I conclude with a statement that the protagonist’s actions, initially captured by the media in moral and ethical terms, are subjected to the phenomenon of commercialization, to which a large part of society acquiesces.